Improving Financial Literacy among Millennials: A Financial Management Perspective - Saputri, Vettyca; Hidayah, Nenden; Susena, Karona; Tarigan, Heskyel (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Financial literacy is a crucial skill for navigating today’s complex economic environment, yet it remains a significant challenge among millennials. As a generation facing increasing financial pressures, understanding key financial principles is essential for making informed decisions and achieving financial well-being. This paper explores the importance of enhancing financial literacy among millennials from a financial management perspective, highlighting the challenges they face and the potential strategies for improvement. By examining existing literature and trends, this study aims to provide insights into the role of financial education and practical steps that can help millennials improve their financial capabilities and make sound financial decisions in an ever-changing world.